Determining stroke and movement profiles in competitive tennis match-play from wearable sensor accelerometry - Perri, T.; Reid, M.; Murphy, A.; Howle, K.; Duffield, R. (The Journal of Strength and Conditioning Research, 2023)
This study determined stroke and movement accelerometry metrics from a wearable sensor and compared between court surface (grass vs. hard) and match outcome (win vs. loss) during competitive tennis match-play. Eight junior high-performance tennis players wore a trunk-mounted global positioning system, with in-built accelerometer, magnetometer, and gyroscope during singles matches on hard and grass courts. The manufacturer software calculated accelerometer-derived total player load (tPL). A prototype algorithm classified forehands, backhands, serves, and "other" strokes, thereby calculating stroke PL (sPL) from individual strokes. Movement PL (mPL) was calculated as the difference between tPL and sPL, with all metrics reported as absolute and relative (min-1, %, and ·stroke). Analysis of accelerometer load and stroke count metrics was performed through a two-way (surface [grass vs. hard] × match outcome [win vs. loss]) analysis of variance (p < 0.05) and effect sizes (Cohen's d). No interaction effects for surface and match outcome existed for absolute tPL, mPL, and sPL (p > 0.05). Increased mPL% featured on grass courts, whereas sPL% was increased on hard courts (p = 0.04, d = 1.18[0.31-2.02]). Elevated sPL·min-1 existed on hard courts (p = 0.04, d = 1.19[0.32-2.04]), but no differences in tPL·min-1 and mPL·min-1 were evident for surface or outcome (p > 0.05). Relative forehand sPL (FH-sPL·min-1) was higher on hard courts (p = 0.03, d = 1.18[0.31-2.02]) alongside higher forehand counts (p = 0.01, d = 1.29[0.40-2.14]). Hitting demands are heightened on hard courts from increased sPL and counts. Conversely, increased mPL% on grass courts likely reflects the specific movement demands from point-play. Physical preparation strategies during training blocks can be tailored toward movement or hitting loads to suit competitive surfaces.